IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH PADA KETERAMPILAN BERBICARA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA DI MA RUHUL AMIN TAHUN AJARAN 2022/2023 - Satria Faithfull Muttabi’ Mi’raj Muchtar; IGA Putu Tuti Indrawati; Ni Luh Sukanadi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
Classroom action research (CAR) in class XI aims to improve students' critical thinking in MA by implementing a problem-based learning model in speaking skills.Ruhul Amin Lamon's academic year is 2022-2023.MA applied to Class XIRuhul Amin Lamongan The data in this study were obtained using observation and tests to observe students' speaking abilities. The data that has been collected was analyzed using descriptive quantitative and descriptive qualitative methods. Based on the research results, this PTK was carried out in two cycles, showing that speaking skills could improve students' critical thinking skills. This can be seen from the average student's speaking skills score in the initial test of 4.14 in the lower category. Cycle I was 5.6 with an almost sufficient category, but in the application to the pre-cycle and cycle I, there were still weaknesses that occurred in the learning process, namely, the student's lack of seriousness in reading the text given, while the alternative solution was given, namely, creating a new, pleasant atmosphere. Based on this solution, there was an increase of 2.22, so in cycle II the average score obtained by students was 7.82 in the "good"